(untitled) (Research, Society and Development, 2023)
Affectivity is present since the beginning of people’s lives, thus, the relevance for the development of human beings is understood. Thus, this study aims to present the importance of affectivity in the teaching and learning process in Early Childhood Education and the relationship between teacher and student. For this, a qualitative approach was used, aiming at a systematic review, in which the SciELO database was used for the selection of studies, using the following descriptors: i) affectivity in early childhood education; ii) affectivity in teaching; iii) affectivity for learning; iV) teacher and student relationship. For the selection of studies, inclusion and exclusion criteria were adopted, delimiting a period between 2017 and 2021, considering more current articles discussed in the educational field. The results showed that among the forty-five studies found, four were selected for data analysis and discussion. These studies pointed out that affectivity is an essential element in Early Childhood Education, given that it is the stage in which children are in development. However, the teaching and learning process needs the family, teachers and the school as a whole. In general, the index of publications on the subject was considered low, in view of the relevance of affectivity for the development of children, a stage in which they are learning and discovering new ways of seeing the world.